Determination of True Ileal Amino Acid Digestibility in the Growing Pig for Calculation of Digestible Indispensable Amino Acid Score (DIAAS). Issue 10 (25th July 2020) - Hodgkinson, Suzanne M; Stein, Hans H; de Vries, Sonja; Hendriks, Wouter H; Moughan, Paul J
ABSTRACT: Digestible indispensable amino acid score (DIAAS) has been recommended by the FAO for the evaluation of protein quality in human foods, but the application of DIAAS is currently limited because of a lack of published data on the true ileal amino acid (AA) digestibility of AAs in foods. The importance of DIAAS is highlighted. To calculate DIAAS, it is necessary to determine the true ileal AA digestibility of human foods using the growing pig as an animal model for the human based on previous FAO recommendations. A method is described in detail in Supplemental Methods to determine the true ileal AA digestibility of foods for humans using the pig as a model for the adult human. Adoption of the method will enable consistency in the development of databases on predicted true ileal AA digestibility in human foods for the calculation of DIAAS.